Pedagogic Interaction in an Online EFL Class at a Junior High School in Depok - Fitria Azifah Dewi; Sisilia Setiawati Halimi (Bina Nusantara University, 2022)
The research was conducted to investigate how the teacher built pedagogic interactions with the students in an online EFL class in Depok, including how the teacher used speech structures, language shifts, and how the students perceived the interactions. The shift to online learning in the pandemic era had affected the quality of learning. Due to the complexity of online learning, interpersonal interactions between teachers and students were frequently overlooked in an online class. Applying exploratory sequential mixed methods, the research was meant to provide findings that could be used to improve the quality of online learning. It began with a qualitative research phase, and then the results of the qualitative phase were used to build into the quantitative phase. Classroom observations, stimulated recalls, and a questionnaire were used to collect the data. The results indicate that the EFL teacher builds his/her interactions by prioritizing pedagogical functions and targeting the students' cognitive domains. The dominant learning cycle is the focus phase with a pedagogical role as an information provider. Intramove is identified as the most frequently occurring code-switching type used for pedagogical, managerial, and technical functions. Translanguaging is also identified which gives rise to productive bilingualism. Overall, the pedagogic interactions that are established by the EFL teacher are well perceived by the students, and they give some suggestions for the quality improvement of EFL online learning so that future classes will be more interactive. More research on the aspects of class interactions during online learning should be carried out to help teachers improve the quality of their online teaching.